E-cycling and health benefits: A systematic literature review with meta-analyses - Riiser, Amund; Bere, Elling; Andersen, Lars Bo; Nordengen, Solveig (Frontiers in Sports and Active Living, 2022)
The objective of the present study is to review and meta-analyze the effect of e-cycling on health outcomes. We included longitudinal experimental and cohort studies investigating the effect of e-biking on health outcomes. The studies were identified from the seven electronic databases: Web of Science, Scopus, Medline, Embase, PsycINFO, Cinahl and SportDiscus and risk of bias was assessed with the revised Cochrane Collaboration Risk of Bias Tool (RoB2). We performed meta-analysis with random effects models on outcomes presented in more than one study. Our study includes one randomized controlled trial, five quasi experimental trials and two longitudinal cohort studies. The trials included 214 subjects of whom 77 were included in control groups, and the cohort studies included 10222 respondents at baseline. Maximal oxygen consumption and maximal power output were assessed in five and four trials including 78 and 57 subjects, respectively. E-biking increased maximal oxygen consumption and maximal power output with 0.48 SMD (95%CI 0.16-0.80) and 0.62 SMD (95%CI 0.24-0.99). One trial reported a decrease in 2-hour post plasma glucoses from 5.53 ± 1.18 to 5.03 ± 0.91 mmol L−1 and one cohort study reported that obese respondents performed 0.21 times more trips on e-bike than respondents with normal weight. All the included studies had a high risk of bias. However, the outcomes investigated in most studies showed that e-biking can improve health. As e-biking has increased massively during the last decade, and has a potential to improve health, it is surprising that there are so few longitudinal studies and only one randomized trial which investigate health effects of e-biking.